The Role of Green HRM and Leadership in Enhancing Pro Environmental Behavior Within Organizations - Derah Sudjaniah; Yustinus Rawi Dandono; Jailani Jailani; Indira Sascha; Nasrullah Nasrullah (Annals of Human Resource Management Research, 2026)
Purpose: This study examines how Green Human Resource Management (Green HRM) and Green Transformational Leadership (GTL) enhance employees' Pro-Environmental Behavior (PEB), with green motivation acting as a mediator and sustainability climate serving as a moderator. Research Methodology: A quantitative, cross-sectional survey was conducted with 390 employees from sustainability-oriented organizations. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to assess the relationships between green HRM, GTL, green motivation, sustainability climate, and PEB. Results: Both green HRM and GTL significantly enhance green motivation, which, in turn, is the strongest predictor of PEB. Furthermore, the sustainability climate moderates and strengthens the indirect effects of green HRM and GTL on PEB. The results highlight that leadership and HR practices, through motivation and a supportive environmental climate, drive employees’ engagement in environmentally responsible behavior. Conclusions: This study demonstrates that employees’ pro-environmental behavior is shaped by a combination of HR practices, leadership, motivation, and organizational climate. The findings emphasize the importance of aligning HRM and leadership strategies with sustainability goals to foster green behavior in organizations. Limitations: This study employed a cross-sectional design, which limits causal inferences. The use of self-reported data could also have introduced biases. Contributions: This study integrates mediation and moderation mechanisms into environmental organizational behavior research, providing a comprehensive model that links green HRM, GTL, green motivation, and sustainability climate to enhance PEB.